2001
DOI: 10.1002/1521-3935(20011101)202:17<3329::aid-macp3329>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Calorimetric Approach to the Kinetic Investigation of the Propylene Bulk Phase Polymerization

Abstract: The bulk phase polymerization of propylene with a silica‐supported metallocene/MAO‐catalyst was kinetically investigated by means of heat flow calorimetry. The principle applicability of the heat flow calorimetry for a reliable kinetic investigation of the bulk process is demonstrated. The polymerization profiles depending on temperature and catalyst concentration have been investigated and have been compared with the slurry process. Activation energy, EA, the order of reaction concerning the catalyst concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…A kinetic investigation of the stereospecific propylene bulk polymerization with the applied industrial metallocene/MAO/SiO 2 -catalyst was already reported in a previous paper. [14] Electron Microscopy…”
Section: Propylene Bulk Polymerization Processmentioning
confidence: 99%
“…A kinetic investigation of the stereospecific propylene bulk polymerization with the applied industrial metallocene/MAO/SiO 2 -catalyst was already reported in a previous paper. [14] Electron Microscopy…”
Section: Propylene Bulk Polymerization Processmentioning
confidence: 99%
“…Korber et. Al., [6,7] working with a commercial calorimeter (RC1 from MettlerToledo) in the propylene polymerization via metallocenes, report comparable results between on-line calorimetry and propylene consumption measurement with a mass flowmeter. Altarawneh et.…”
Section: Introductionmentioning
confidence: 81%
“…This method (calorimetric) has been employed successfully in a variety of polymerization reactions. [4][5][6][7][8][9] Rincón et. Al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This method (calorimetric) has been employed successfully in a variety of polymerization reactions [4][5][6][7][8][9]. In a recent report [9], the calorimetric method has been used for the monitoring of ethylene polymerization via metallocenes in a laboratory reactor.…”
Section: Introductionmentioning
confidence: 99%